Urban heat island experience, control measures and health impact: A survey among working community in the city of Kuala Lumpur - Wong, Li Ping; Alias, Haridah; Aghamohammadi, Nasrin; Aghazadeh, Sima; Sulaiman, Nik Meriam Nik (Elsevier, 2017)
This study aimed to provide evidence regarding the health effects of urban heat island (UHI) in Kuala Lumpur city, as well as its associated contributing factors. A total of 1050 working community in Kuala Lumpur responded to the survey. Rating the total adverse health experiences with scores ranging from 0 to 14, the median rating was 11 [interquartile range (IQR) 5–11]. Multivariate analysis revealed significantly higher odds of total adverse health experience score (Odds Ratio [OR] = 18.297; 95% Confidence Interval [CI] 11.627–28.794) were reported among participants with scores for measures to reduce UHI of 0–13 than for those with scores of 14–23. Duration of working in the city, and being in high-rise and high-density buildings were among other significant factors that also contribute to adverse health experiences. The study found a lack of shaded lanes in active transport promotion, green vegetation, and lack used of appropriate building materials to reduce UHI. There is a strong association between adverse health effects of UHI and low measures to reduce UHI effects. Our study contributes useful empirical insights of the importance of undertaking UHI control measures and introducing vegetation in cities, which should be included in the strategic plan to address urban heat.